Mn3O4 encapsulated in hollow carbon spheres coated by graphene layer for enhanced magnetization and lithium-ion batteries performance - Thauer, Elisa; Shi, Xiaoze; Zhang, Shuai; Chen, Xuecheng; Deeg, Lukas; Klingeler, Rüdiger; Wenelska, Karolina; Mijowska, Ewa (Energy, 2021)
We report a facile method to prepare graphene coated core-shell Mn3O4 nanoparticles encapsulated in hollow carbon sphere (HCS) (G-HCS-Mn3O4). HCSs were firstly prepared at high temperature based on a core-shell template, leading to good electrical conductivity of 21.6 S m−1. The porous shells of HCSs provide passage for the manganese precursors and big cavities to store the inorganic particles. Furthermore, the Mn3O4 filling is proven by magnetization measurements showing characteristic ferrimagnetic ordering at 41 K. Electrochemical studies show that the Mn3O4 nanoparticles encapsulated in HCS are electrochemical active and there is full access to the theoretical capacity of Mn3O4. When used as anode material, G-HCS-Mn3O4 impresses by superior properties compared to pristine HCS. It can achieve a high specific charge capacity of 557 mAh g−1 at the current density of 100 mA g−1 and even 374 at 500 mA g−1. The approach of exploiting HCS-based nanocomposites can be expanded to encapsulate a variety of inorganic materials with controllable size and amount, providing new choices for electrode materials and other potential applications.
Available online 23 November 2020
Im Titel sind die Zahlen "3" und "4" tiefgestellt
Gesehen am 09.09.2021